2017
DOI: 10.18632/oncotarget.21811
|View full text |Cite
|
Sign up to set email alerts
|

Low fT3 is associated with diminished health-related quality of life in patients with acute coronary syndrome treated with drug-eluting stent: a longitudinal observational study

Abstract: Acute coronary syndrome (ACS) patients with low triiodothyronine (T3) syndrome characterized by low free T3 (fT3) levels with normal thyroxine (T4) and thyroid-stimulating hormone (TSH) have a higher rate of death. The impact of fT3 on Health related quality of life (HRQOL) in patients with ACS is still unknown. 528 ACS patients treated with drug-eluting stent (DES) were included in this prospective, observational study. Patients were classified into low fT3 group (n=126) and normal fT3 group (n=402) according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…A study on mild cognitive impairment and dementia showed that patients with relatively high T3 levels showed impairment in memory and visuospatial and executive functions [73]. However, patients with acute coronary syndrome having low T3 levels had a poorer health-related quality of life (including general health, social functioning, and role emotional) than those with normal levels at a 1-year follow-up [74]. A study on subjective cognitive decline showed that higher T3 levels were associated with better verbal memory performance (immediate and delayed recall tasks) in APOE ε4 carriers [75].…”
Section: Discussionmentioning
confidence: 99%
“…A study on mild cognitive impairment and dementia showed that patients with relatively high T3 levels showed impairment in memory and visuospatial and executive functions [73]. However, patients with acute coronary syndrome having low T3 levels had a poorer health-related quality of life (including general health, social functioning, and role emotional) than those with normal levels at a 1-year follow-up [74]. A study on subjective cognitive decline showed that higher T3 levels were associated with better verbal memory performance (immediate and delayed recall tasks) in APOE ε4 carriers [75].…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests an inverse relationship between serum BNP and serum T3 levels in patients without hyperthyroidism (18). We hypothesized that low T3 status could serve as a prognostic indicator in AMI since there is a negative relationship between fT3 and NT-pro-BNP (18).…”
Section: Acute Myocardial Infarction (Ami) Is a Leading Cause O F M O R B I D I T Y A N D M O R T A L I T Y W O R L D W I D E ( 1 )mentioning
confidence: 97%
“…The literature suggests an inverse relationship between serum BNP and serum T3 levels in patients without hyperthyroidism (18). We hypothesized that low T3 status could serve as a prognostic indicator in AMI since there is a negative relationship between fT3 and NT-pro-BNP (18). Therefore, the aims of this study were to investigate the association between low fT3 levels and prognosis and the relationship between fT3 and NT-pro-BNP levels in patients with AMI.…”
Section: Acute Myocardial Infarction (Ami) Is a Leading Cause O F M O R B I D I T Y A N D M O R T A L I T Y W O R L D W I D E ( 1 )mentioning
confidence: 98%
See 1 more Smart Citation
“…Ö³ çì³íè ôóíêö³¿ îñ³ «ã³ïîòàëàìóñ-ã³ïîô³ç-ùèòî-ïîä³áíà çàëîçà» íàçèâàþòüñÿ ñèíäðîìîì «íèçüêîãî» òðèéîäòèðîí³íó. Ïåðåäáà÷àºòüñÿ, ùî äàíèé ñòàí ìîaeå áóòè àäàïòèâíèì êîìïåíñàòîðíèì ìåõàí³çìîì äëÿ çáåðåaeåííÿ ñïîaeèâàííÿ åíåð㳿 òà âåëè÷èíà çì³íè êîíöåíòðàö³¿ T 3 âàð³þº çàëåaeíî â³ä òÿaeêîñò³ çàõâîðþâàííÿ [9]. Ó [10][11][12] êðèòåð³ºì âèçíà÷åííÿ ñèíäðîìó «íèçüêîãî» òðèéîäòèðîí³íó º íèaeíÿ ìåaeà íîðìè Ò 3â ( 2,5 ïìîëü/ë) çà íîðìàëüíèõ ð³âí³â Ò 4â ³ ÒÒÃ.…”
Section: ðåçóëüòàòè äîñë³äAeåííÿunclassified